Post head injury neurobehavioral sequelae: severity among alcoholics - Sreemathyamma, Sunilkumar B.; Asher, Prasanth; Baburaj, Palamkunnil T.; Kutty, Raja K.; Beevi, Sharmad Mohammed Haneefa Suharban; Peethambaran, Anilkumar; Leela, Sureshkumar Kunjini (International Surgery Journal, 2020)
Background: Alcohol use and traumatic brain injury (TBI) are closely linked public health problems. Alcohol intoxication is one of the major risk factor for TBI, and is a main determinant of prognosis in terms of mortality and functional outcome. The aim of the study is to find out the impact of alcoholism in the neurobehavioral outcome following TBI. Methods: A total of 150 head injury patients were divided into two groups: alcoholics and non-alcoholics, and evaluated between six weeks to one year after injury using the revised neurobehavioral rating scale by Levin et al (NRS-R) for the evaluation of neurobehavioral sequelae and the outcome was compared between groups. Results: The study showed significant difference between the groups indicating that the neurobehavioral sequelae were more in the chronic alcoholics group. In the comparison of individual factors, all except factors III (negative symptoms) and IV (mood and affect) were found to be significantly different. The factors I (executive), II (positive symptoms), V (oral and motor), and VI (not loading on any of the factors) were significant at 0.01 level. Conclusions: Chronic alcoholism significantly increases the risk of developing neurobehavioral sequelae after traumatic brain injury.